THE REPRESENTATION OF INSTITUTIONAL RACISM IN THE SAGA NOVEL THE AMERICAN PALACE-BLESS THIS HOUSE BY EVAN HAROLD RHODES - Wini Marttrianti, - (2007)
This research paper is a report on a textual analysis of a saga novel The American Palace-Bless This House written by Evan Harold Rhodes. The study aims at finding the answer to the main question: "How is the institutional racism represented in the novel?" A descriptive method with a qualitative approach is applied to answer the research question. The data are collected in the form of textual evidence. The data gained were categorized and further analyzed by means of Bill Ashcroft, Gareth Griffith and Hellen Tiffm's theoretical proposition of the colonizer and the colonized within the Postcolonial perspective. The result of the study discloses four main categories of White people. They are elaborated from the White people characters and their attitudes toward the Indian and Black people characters. Those categories are: the colonizers, the masters, the government officials and the subcontractors. Framed by the Postcolonial perspective and with reference to Bill Ashcroft, Gareth Griffith and Hellen Tiffin's theory, the findings indicate two opposing constructions in the text that positions the White people as the colonizer or the oppressor and the Non-White people as the colonized or the oppressed. Therefore, it is implied that the White people are superior to the Non-White people.